Evaluasi Akurasi Modul GNSS Low-Cost Unicore UM982 terhadap Receiver GNSS Komersial pada Pengukuran Statik - Muhammad Khairul Iman; Henri Kuncoro (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The high cost of professional geodetic GNSS receivers limits accessibility for educational institutions and survey practitioners with constrained budgets. The low-cost Unicore UM982 GNSS module offers a promising alternative; however, its technical feasibility for static observations requires evaluation. This study evaluates the positioning accuracy of the Unicore UM982 against a commercial Trimble R2 receiver as the reference benchmark in static GNSS measurements. Observations were conducted across the Bandung metropolitan area across varying baseline lengths to the CORS CANG station, categorized into short (<5 km), medium (5–10 km), and long (>10 km) baselines. RINEX data were post-processed using Trimble Business Center (TBC), establishing Trimble R2 Most Probable Value (MPV) coordinates as ground truth. Accuracy was evaluated using RMSE, standard deviation, coefficient of determination (R2), and paired t-tests. Results indicate that the Unicore UM982 achieves coordinate accuracy comparable to the Trimble R2 on short-to-medium baselines, meeting geodetic control survey tolerances. Paired t-tests showed no statistically significant differences on short baselines. However, baseline length explained only 3.35% of horizontal RMSE variance (R2 = 0.0335), demonstrating that site-specific errors such as multipath and satellite geometry dominated fluctuations. In conclusion, the Unicore UM982 provides a viable, cost-effective solution for centimeter-level geodetic positioning.